Construction Accidents via Integrating Building Information Modelling (BIM) with Emerging Digital Technologies a Review - Ammad, S. (Institute of Electrical and Electronics Engineers Inc., 2021)
In recent decades, digital technologies have advanced in various parts of the world. In addition, as these digital technologies progress, new types of accidents have emerged. To map global research findings on construction health and safety technologies, it has been our endeavour to review those technologies utilized in the field of construction health and safety management. This paper reviews publication that has been published in journals and the International Conference on Construction and Building Engineering which have been compiled to reveal emerging research trends. A compilation of all the studies is discussed to give a better understanding. Â© 2021 IEEE.